Safeguarding children and strengthening families through the application and utilization of family group decision making: A systematic review protocol - Collen Mafira Ngadhi; Shenaaz Wareley; Patrick Joseph; Chanté Johannes; Gary Spolander; Nicolette Vanessa Roman (PLoS ONE, 2026)
Children and families often face adversities that require whole-family interventions to promote well-being. Traditional child welfare models often demonstrate insufficient family involvement in decision-making, leading to gaps in safeguarding efforts. The Family Group Decision-Making (FGDM) model emerged as an intervention that empowers families to identify and develop solutions to their challenges. The aim of this systematic review protocol is to assess the application and utilisation of FGDM with a specific focus on synthesizing evidence that can inform its implementation within developing country contexts, where child welfare systems may face unique challenges. The Population, Intervention, Comparison, Outcome (PICO) framework will be used to define the research question. The inclusion and exclusion criteria will be based on studies that focus on FGDM (including its variants), publications from 2014 to December 2024, and studies published in English. Qualitative and quantitative design studies will be included. EBSCOhost (CINAHL, Masterfile Premier, MEDLINE, Academic Search Ultimate), PubMed, Sabinet, Wiley Online Library, Scopus, and Web of Science will be accessed through the University of the Western Cape’s library catalogue. Search terms will be combined with relevant keywords to create search strings using Boolean operators. The Critical Appraisal Skills Programme (CASP) checklists will be used for appraisal. Three independent reviewers will screen articles, a fourth reviewer consulted in case of disagreements. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) flowchart will illustrate the search, screening, and selection process. Data will be qualitatively synthesized using thematic analysis. This protocol is registered on Open Science Framework https://doi.org/10.17605/OSF.IO/B3TH8 .